ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU SEMEN PADA CV. DUA BERSAUDARA KUPANG - Andini Anggiani Putri Kadja; Christien C Foenay; Ronald P C Fanggidae (Journal of Management Small and Medium Enterprises (SMEs), 2019)
The purpose of this study was to determine the inventory control of raw material (cement) inCV. Dua Bersaudara, Kupang. The method used is the Economic Order Quantity, SafetyStock and ReOrder Point. The results of the study showed that the total cost of cement rawmaterial inventory using the EOQ method is smaller than the method used by the company.CV. Dua Bersaudara, Kupang should try to apply the EOQ method in terms of raw materialinventories so that the company can minimize inventory costs. Keywords: Economic Order Quantity, Safety Stock and Re-Order Point